Polyacid-based material, preparation method and application thereof, and electrode

The preparation of polyacid-based nanocluster materials with dimer structures through hydrothermal synthesis technology, solving the problem of easy shedding of electrodes of polyacid-based materials and low efficiency of degradation of MDEA, and achieving efficient MDEA degradation effect and long-term material time stability.

CN119461584AActive Publication Date: 2025-02-18CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311012372.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-11
Publication Date
2025-02-18
Estimated Expiration
2043-08-11

AI Technical Summary

Technical Problem

The existing polyacid-based material modified electrodes are prone to fall off and have low degradation efficiency for N-methyldiethanolamine (MDEA).

Method used

Hydrothermal synthesis technology is used to prepare polyacid-based supramolecular materials with electrocatalytic degradation properties, by combining with 4,4'-(1,3-propylene)bispyridine or 1,4-bis(imidazole-1-yl) Butane ligand, Na9(A-α-PW9O34)·7H2O, and metal iron salt are reacted to form a polyacid-based nanocluster material with a dimer structure.

Benefits of technology

The high efficiency of polyacid-based nanocluster material modified electrodes in degrading MDEA is achieved. The degradation rate of MDEA can reach 99.92%, and the material remains stable after use for more than 10 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461584A_ABST
    Figure CN119461584A_ABST
Patent Text Reader

Abstract

The invention relates to the field of degradation of N-methyldiethanolamine (MDEA), and discloses a multi-acid-group crystal material, a preparation method and application thereof, and an electrode. The chemical formula of the multi-acid-group material is [Fe2 (H6P2W22O78)]. P (CxHyNz) r.qH2O, and the chemical formula of the multi-acid-group material is as shown in the specification. Wherein p is an integer between 1 and 4; x is an integer from 10 to 13; y is 15 or 16; z is an integer between 2 and 4; r is an integer between 2 and 4; q is a natural number between 0 and 3. The multi-acid-group crystal material has the effect of electro-catalytic degradation of MDEA, and the degradation rate of MDEA can reach 99% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of degradation of N-methyldiethanolamine (MDEA), and in particular to a polyacid-based material, a preparation method and application thereof, and an electrode. Background Art

[0002] N-Methyldiethanolamine (MDEA), as an alkanolamine alkaline solvent, has been widely used in the field of decarbonization in recent years due to its good acid gas absorption performance. However, with the continuous increase in the demand for amine liquid concentration, problems such as amine liquid foaming, deterioration and failure have also frequently occurred. Many companies have experienced amine liquid foaming leading to liquid blocking and tower flushing, amine liquid leakage and other problems. Therefore, with the large-scale use of amine liquid, high-concentration waste amine liquid is recycled, and the leaked trace organic amine is effectively treated to avoid direct mixing with other wastewaters to increase the difficulty of wastewater treatment and reduce pollution and harm to organisms and the environment.

[0003] MDEA wastewater is mainly degraded by adsorption, chemical oxidation and biological direct degradation. Although the above methods have certain effects on the degradation of MDEA, they have disadvantages such as low degradation rate, excessive dosage of oxidants, complex operation and low safety performance. At present, electrochemical methods are rarely used to degrade MDEA. Electrochemical water treatment technology is a green water treatment technology. Its main principle is to use potential difference to regulate the flow of electrons so that pollutants can complete the degradation or transformation process at the electrode interface or in the solution to achieve water purification. The core of electrochemical degradation lies in the research of electrocatalysts.

[0004] Polyacids are in a completely oxidized state under normal conditions and can exist in a completely or incompletely protonated form. At the same time, the presence of metal ions in polyacids can provide empty orbitals to accept electrons, have good redox properties, and can be used as excellent electrocatalysts. However, studies have found that because classical polyacids are soluble in water and some organic solvents, they are easily detached and unstable when used as catalyst materials to modify electrodes, and the catalyst life is short. At the same time, the specific surface area of ​​classical polyacids themselves is very small, the surface active sites are few and easy to aggregate, which limits the performance of their inherent catalytic performance. Therefore, in order to solve the problem of classical polyacids being easily detached when used as catalyst materials to modify electrodes, a polyacid-based material that can effectively degrade MDEA and its preparation method are needed. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of easy detachment of polyacid-based material modified electrodes and low efficiency in degrading MDEA in the prior art, and to provide a polyacid-based material capable of effectively degrading MDEA and a preparation method thereof.

[0006] In order to achieve the above object, the present invention provides a polyacid-based crystalline material in a first aspect, wherein the chemical formula of the polyacid-based material is [Fe2(H6P2W22 O 78 )]·p(C x H y N z ) r qH2O;

[0007] Among them, p is an integer between 1 and 4; x is an integer between 10 and 13; y is 15 or 16; z is an integer between 2 and 4; r is an integer between 2 and 4; and q is a natural number between 0 and 3.

[0008] A second aspect of the present invention provides a method for preparing a polyacid-based crystalline material, the method comprising:

[0009] (1) mixing a polyacid, an iron salt, a ligand and water to obtain a mixture;

[0010] (2) subjecting the mixture to a chemical reaction and obtaining the polyacid-based crystalline material after post-treatment.

[0011] The third aspect of the present invention provides a polyacid-based crystalline material prepared by the method described in the second aspect of the present invention.

[0012] The fourth aspect of the present invention provides an application of the polyacid-based crystalline material described in the first aspect or the third aspect of the present invention in the field of degradation of N-methyldiethanolamine.

[0013] The fifth aspect of the present invention provides an electrode, which includes the polyacid-based crystalline material described in the first aspect or the third aspect of the present invention.

[0014] Through the above technical solution, the beneficial effects of the present invention are as follows:

[0015] 1. The present invention adopts a simple hydrothermal synthesis technology and utilizes 4,4′-(1,3-propanediyl)bipyridine ligand or 1,4-bis(imidazole-1-yl)butane ligand, Na9(A-α-PW9O 34 )·7H2O, and metal iron salts successfully prepared polyacid-based supramolecular materials with electrocatalytic degradation performance; Keggin-type vacancy polyacid (PW9O 34 ) 9- First, obtain the WO6 polyhedron (PW 11 ) unit, and then coordinates with the iron atom to form the iron atom monosubstituted type (FePW 11 ) unit, adjacent (FePW 11 The iron atom in the unit is connected to the terminal oxygen atom of the other party to form a novel dimer structure such as Figure 1 As shown, measured by Diamond software, the length of the dimer reaches 1.9 nm.

[0016] 2. The glassy carbon electrode modified with polyacid-based nanocluster materials having electrocatalytic performance prepared by the present invention. Using an electrochemical workstation, under a standard three-electrode system, the glassy carbon coated with the polyacid-based nanocluster materials is used as a working electrode, while a platinum wire is used as a counter electrode, and Ag / AgCl is used as a reference electrode. In a Na2SO4 solution containing 0.05 mol / L MDEA, the electrocatalytic oxidation degradation efficiency of the glassy carbon electrode modified with polyacid-based nanocluster materials can reach 99.92%, which has good application value in the degradation of MDEA.

[0017] 3. The polyacid-based nanocluster material with electrocatalytic performance prepared by the present invention has stable performance when catalyzing the degradation reaction of MDEA and can be used continuously for more than 10 hours. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a schematic structural diagram of a polyacid-based crystalline material having a dimer structure for electrocatalytic oxidation degradation of MDEA prepared in Example 1 of the present invention;

[0019] Figure 2 This is a schematic diagram of powder X-ray diffraction of a polyacid-based crystalline material having a dimer structure for electrocatalytic oxidation degradation of MDEA prepared in Example 1 of the present invention;

[0020] Figure 3 This is a schematic diagram of the infrared spectrum of a polyacid-based crystalline material having a dimer structure for electrocatalytic oxidation degradation of MDEA prepared in Example 1 of the present invention;

[0021] Figure 4 is an X-ray single crystal diffraction pattern of a polyacid-based crystalline material having a dimer structure for electrocatalytic oxidation degradation of MDEA prepared in Example 7 of the present invention;

[0022] Figure 5 This is a thermogravimetric diagram of a polyacid-based crystalline material having a dimer structure for electrocatalytic oxidation degradation of MDEA prepared in Example 1 of the present invention;

[0023] Figure 6 This is a cyclic voltammetry curve of a polyacid-based crystalline material having a dimer structure for electrocatalytic oxidation degradation of MDEA prepared in Example 1 of the present invention;

[0024] Figure 7 This is a chromatogram of MDEA before reaction in a polyacid-based crystalline material having a dimer structure for electrocatalytic oxidation degradation of MDEA prepared in Example 1 of the present invention;

[0025] Figure 8This is a chromatogram after the reaction of MDEA in a polyacid-based crystalline material having a dimer structure for electrocatalytic oxidation degradation of MDEA prepared in Example 1 of the present invention.

[0026] Fig. 9 It is the IT curve of the polyacid-based crystal material, indicating that the polyacid-based crystal material remains stable after 10 hours of use. Where i represents the ordinate Current Density. DETAILED DESCRIPTION

[0027] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0028] The first aspect of the present invention provides a polyacid-based crystalline material, wherein the chemical formula of the polyacid-based material is [Fe2(H6P2W 22 O 78 )]·p(C x H y N z ) r qH2O;

[0029] Among them, p is an integer between 1 and 4; x is an integer between 10 and 13; y is 15 or 16; z is an integer between 2 and 4; r is an integer between 2 and 4; and q is a natural number between 0 and 3.

[0030] In some embodiments of the present invention, preferably, the crystal system of the polyacid-based crystal material is triclinic; the space group of the polyacid-based crystal material is P-1: the single package parameters of the polyacid-based crystal material include: a=11.671(12)-12.148(3), b=13.394(2)-13.591(13), c=17.080(3)-18.132(18), α=86.366(3)-101.532(5), β=74.056(2)-95.030(5), γ=67.280(2)-108.957(5), V=2540.0(8)-2547.9(4), Z=1. It can be determined by X-ray diffraction.

[0031] In the present invention, preferably, the polyacid-based crystalline material is [Fe2(H6P2W 22 O 78 )]·4(C 13 H 15N2)2 or [Fe2(H6P2W 22 O 78 )]·(C 10 H 16 N4)4·3H2O.

[0032] In the present invention, the polyacid-based crystalline material has a dimer structure and can be Figure 2 The X-ray diffraction pattern shown is characteristic of this structure.

[0033] A second aspect of the present invention provides a method for preparing a polyacid-based crystalline material, the method comprising:

[0034] (1) mixing a polyacid, an iron salt, a ligand and water to obtain a mixture;

[0035] (2) subjecting the mixture to a chemical reaction and obtaining the polyacid-based crystalline material after post-treatment.

[0036] In some embodiments of the present invention, preferably, in step (1), the iron salt is selected from ferrous acetate and ferrous chloride, and is used to provide iron ions in the polyacid-based crystalline material.

[0037] In some embodiments of the present invention, preferably, the polyacid is a Keggin-type vacancy phosphotungstic acid; preferably selected from Na9(A-α-PW9O 34 )·7H2O.

[0038] In some embodiments of the present invention, preferably, the ligand is selected from pyridine-containing or imidazole-containing compounds, preferably 4,4′-(1,3-propanediyl)bipyridine or 1,4-bis(imidazol-1-yl)butane, to provide the ligand component in the polyacid-based crystalline material.

[0039] In some embodiments of the present invention, preferably, in step (1), the molar ratio of the polyacid to the iron salt is 1:3-6.

[0040] In some embodiments of the present invention, preferably, in step (1), the molar ratio of the polyacid to the ligand is 1:2-3.

[0041] In some embodiments of the present invention, preferably, in step (1), the pH value of the mixture is 2.5-4.5, which can make the chemical reaction proceed smoothly while suppressing the occurrence of side reactions to the greatest extent.

[0042] In some embodiments of the present invention, preferably, in step (2), the temperature of the chemical reaction is 130-140° C. This allows the chemical reaction to proceed fully while minimizing the amount of by-products generated.

[0043] In some embodiments of the present invention, preferably, in step (2), the reaction time of the chemical reaction is 5-7 days, so that the chemical reaction can be fully carried out and the yield of the polyacid-based crystalline material can be maximized.

[0044] In the present invention, the post-treatment process includes: cooling to room temperature, dissolving impurities using ultrasound, washing with deionized water and drying to obtain a dry product, which can purify the polyacid-based crystalline material.

[0045] The third aspect of the present invention provides a polyacid-based crystalline material prepared by the method described in the second aspect of the present invention.

[0046] The polyacid-based crystalline material may have the aforementioned dimer structure, which will not be described in detail herein.

[0047] The fourth aspect of the present invention provides an application of the polyacid-based crystalline material described in the first aspect or the third aspect of the present invention in the field of degradation of N-methyldiethanolamine.

[0048] The fifth aspect of the present invention provides an electrode, which includes the polyacid-based crystalline material described in the first aspect or the third aspect of the present invention.

[0049] The present invention will be described in detail below through examples. In the following examples, the raw materials sodium tungstate, iron salt, 4,4′-(1,3-propanediyl)bipyridine, phosphoric acid, and 1,4-bis(imidazol-1-yl)butane were purchased from Aladdin Reagent Co., Ltd.

[0050] Polyacid Na9(A-α-PW9O 34 )·7H2O synthesis steps: 120g sodium tungstate is dissolved in 150g water, 4mL phosphoric acid is added, and then 22.5mL glacial acetic acid is added and stirred continuously to obtain a white precipitate, which is filtered and dried. This synthesis step is a commonly used method in the art (see the preparation method disclosed in "Multinuclear transition metal sandwich-type polytungstate derivatives for enhanced electrochemical energy storage and bifunctional electrocatalysis performances" (XY Ma, KYu, J Yuan, et al., Inorg. Chem., 2020, 59 (7): 5149-5160)).

[0051] Example 1

[0052] Polyacid Na9(A-α-PW9O 34)·7H2O, iron salt Fe(OAc)2, 4,4′-(1,3-propanediyl)bipyridine ligand and 10 mL of deionized water were stirred and mixed for 1.5 hours to obtain a mixture, and the pH value was adjusted to 2.5 with 2 M HCl;

[0053] Wherein, the molar ratio of polyacid to iron salt is 1:3;

[0054] The molar ratio of the polyacid to the 4,4'-(1,3-propanediyl)bipyridine ligand is 1:3;

[0055] The mixture was reacted at 140°C for 7 days and then taken out. After cooling to room temperature, the impurities were dissolved by ultrasound and washed with deionized water. After washing and drying the product, yellow flaky crystals were obtained, which were determined by X-ray diffraction analysis to be polyacid-based crystal materials with a yield of 53% [based on Na9(A-α-PW9O 34 )].

[0056] Example 2

[0057] High-purity ammonia was prepared in the same manner as in Example 1, except that the iron salt was ferric chloride. The yield of the polyacid-based crystalline material was 37% [based on Na9(A-α-PW9O 34 )].

[0058] Example 3

[0059] High-purity ammonia was prepared in the same manner as in Example 1, except that the molar ratio of polyacid to iron salt was 1:6. The yield of polyacid-based crystalline material was 23% [based on Na9(A-α-PW9O 34 )].

[0060] Example 4

[0061] High-purity ammonia was prepared in the same manner as in Example 1, except that the molar ratio of the polyacid to the 4,4'-(1,3-propanediyl)bipyridine ligand was 1:2. The yield of the polyacid-based crystalline material was 45% [based on Na9(A-α-PW9O 34 )].

[0062] Example 5

[0063] High purity ammonia was prepared in the same manner as in Example 1, except that the pH of the mixture was 4.5. The yield of polyacid-based crystalline material was 33% [based on Na9(A-α-PW9O 34 )].

[0064] Example 6

[0065] High-purity ammonia was prepared in the same manner as in Example 1, except that the mixture was reacted at 130°C for 7 days before being taken out. The yield of the polyacid-based crystalline material was 21% [based on Na9(A-α-PW9O 34 )].

[0066] Example 7

[0067] High-purity ammonia was prepared in the same manner as in Example 1, except that the ligand was 1,4-bis(imidazol-1-yl)butane. The yield of the polyacid-based crystalline material was 32% [based on Na9(A-α-PW9O 34 )].

[0068] Comparative Example 1

[0069] According to the report "Research Progress of N-Methyldiethanolamine Wastewater Treatment Technology" ("Modern Chemical Industry" Vol. 42 No. 12), the main treatment technologies for N-methyldiethanolamine (MDEA) wastewater and their MDEA degradation rates are:

[0070] Biological method: 98.42%; electrolysis method: 97%; oxidant direct oxidation technology: 85%; technical coupling: 96%.

[0071] Performance Testing

[0072] (1) Structural characterization of polyacid-based crystalline materials

[0073] The polyacid-based crystalline materials prepared in Examples 1 and 7 respectively have the chemical formulas of [Fe2(H6P2W 22 O 78 )]·4(C 13 H 15 N2)2 and [Fe2(H6P2W 22 O 78 )]·(C 10 H 16 N4)4·3H2O, the molecular formulas are C 52 H 66 Fe2N8O 78 P2W 22 and C 40 H 70 Fe2N 16 O 81 P2W 22 .

[0074] In the polyacid-based crystalline materials prepared in Examples 1 and 7, two single-vacancy (PW 11 ) unit encapsulates a (Fe2O2) unit in the middle, thus forming a nanocluster based on a dimer structure (such as Figure 1The diverse metal atoms and abundant oxygen atoms provide abundant active centers for the oxidative degradation of MDEA.

[0075] The polyacid-based crystal materials with good quality were selected under a high-power microscope and fixed on an X-ray single crystal diffractometer for data collection, wherein the X-ray diffraction source was Mo target Kα ray. The dimer structure and chemical formula were analyzed using the SHELXL-2018 / 3 software package, and the crystal structure was initially solved using the direct method, and the least squares method F was used to obtain the dimer structure and chemical formula. 2 The data were refined, non-hydrogen atoms in the crystal structure were anisotropically refined, and C and N atoms were hydrogenated using the theoretical hydrogenation method.

[0076] The X-ray crystallographic parameters of the polyacid-based crystalline materials obtained in Examples 1 and 7 are shown in Tables 1 and 2, respectively.

[0077] Table 1

[0078]

[0079] Table 2

[0080]

[0081]

[0082] X-ray single crystal diffraction analysis shows that the polyacid-based crystalline material [Fe2(H6P2W 22 O 78 )]·4(C 13 H 15 N2)2 can reach the nanometer size level, and the basic composition structure includes single iron atom substitution (FePW 11 ) units and free 4,4′-(1,3-propanediyl)bipyridine ligands. Figure 1 The schematic diagram of the structure of the polyacid-based crystal material prepared in Example 1, wherein the Fe atom is connected to the oxygen atom in the polyacid to present a six-coordinated mode, and the bond length of the Fe-O bond is 1.927(15)-

[0083] Figure 2 The powder X-ray diffraction spectrum of the polyacid-based crystalline material prepared in Example 1; Figure 2 It can be seen that the diffraction peaks of XRD are consistent with the theoretical XRD spectrum, indicating that the synthesized polyacid-based crystalline material is pure phase.

[0084] Figure 3 This is the infrared spectrum of the polyacid-based crystalline material prepared in Example 1. Figure 3 It can be seen that at 3475cm -1The peak in the range is attributed to the stretching vibration of OH, at 3079 cm -1 The range corresponds to the CH stretching vibration peak on the organic ligand, which is 1504-1639cm -1 The peaks at 1057 cm-1 are attributed to the C=C and C=N stretching vibrations of the organic ligands. -1 The peak at 960 cm-1 is the stretching vibration peak of PO in the polyacid anion. -1 It is attributed to the absorption peak of W=O at 802cm -1 The absorption peak at is attributed to the absorption of WOW. The above characteristic absorption peaks can also prove Figure 2 The chemical structure of the polyacid-based crystalline material having a dimer structure is shown.

[0085] Figure 4 Schematic diagram of the structure of the polyacid-based crystalline material prepared in Example 7. Figure 4 It can be seen that X-ray single crystal diffraction analysis shows that the nano-sized polyacid-based crystalline material [Fe2(H6P2W 22 O 78 )]·(C 10 H 16 The basic structure of N4)4·3H2O includes single substitution of iron atom (FePW 11 ) units and free 1,4-bis(imidazol-1-yl)butane ligands.

[0086] Figure 5 This is a thermogravimetric diagram of a polyacid-based crystalline material having a dimer structure prepared in Example 1. Figure 5 It can be seen that when the temperature rises from room temperature to 345°C, the mass of the polyacid-based crystalline material remains stable. When the temperature continues to rise, the polyacid-based crystalline material loses weight significantly. This is due to the collapse of the 4,4′-(1,3-propanediyl)bipyridine ligand and part of the metal skeleton.

[0087] (2) Verification of the effect of polyacid-based crystalline materials on MDEA degradation

[0088] Using an electrochemical workstation, 7 mg of polyacid-based crystalline material [Fe2(H6P2W 22 O 78 )]·4(C 13 H 15N2)2 was dispersed in an ethanol solution containing Nafion solution, and then added dropwise to glassy carbon as a working electrode after ultrasonic homogenization. Platinum wire was used as a counter electrode, and Ag / AgCl was used as a reference electrode. In a Na2SO4 solution containing 0.05 mol / L MDEA, the electrocatalytic oxidation degradation efficiency of MDEA on the glassy carbon electrode modified with polyacid-based nanocluster materials could reach 99.92%. When the [Fe2(H6P2W 22 O 78 )]·4(C 13 H 15 When the dosage of [Fe2(H6P2W 22 O 78 )]·4(C 13 H 15 N2)2 is replaced by [Fe2(H6P2W 22 O 78 )]·(C 10 H 16 N4)4·3H2O was used to carry out the electrocatalytic oxidation reaction of the above MDEA, and the degradation efficiency was 99.41%.

[0089] Figure 6 The cyclic voltammetry curve of the polyacid-based crystalline material prepared in Example 1; Figure 6 It can be seen that triethanolamine has an oxidation peak in the electrolyte but no reduction peak, and the oxidation peaks are all in the potential range of 0.87 V, indicating that MDEA undergoes an irreversible direct electrocatalytic oxidation reaction.

[0090] Figure 7 and Figure 8 The liquid chromatograms of the polyacid-based crystalline material prepared in Example 1 before and after the MDEA reaction are shown respectively; Figure 8 It can be seen that compared with Figure 7 , Figure 8 The peak area corresponding to MDEA in the solution was significantly reduced, indicating that an obvious oxidation reaction occurred in MDEA.

[0091] Fig. 9 1 is the IT curve of the polyacid-based crystalline material prepared in Example 1, indicating that the polyacid-based crystalline material remains stable after being used for 10 hours, indicating that the polyacid-based crystalline material is firmly attached to the glassy carbon electrode during this time and does not fall off.

[0092] In summary, the embodiments of the technical solution of the present invention can efficiently prepare polyacid-based crystalline materials, and the chemical formulas thereof are [Fe2(H6P2W 22 O 78 )]·4(C 13 H 15N2)2 and [Fe2(H6P2W 22 O 78 )]·(C 10 H 16 N4)4·3H2O, the polyacid-based crystal material has the effect of electrocatalytic degradation of MDEA, and can make the degradation rate of MDEA reach more than 99%, which has significantly better effect than the existing technology.

[0093] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A polyacid-based crystalline material, characterized in that: The chemical formula of the polyacid-based material is [Fe2(H6P2W 22 O 78 )]·p(C x H y N z ) r qH2O; Among them, p is an integer between 1 and 4; x is an integer between 10 and 13; y is 15 or 16; z is an integer between 2 and 4; r is an integer between 2 and 4; and q is a natural number between 0 and 3.

2. The polyacid-based crystalline material according to claim 1, wherein The crystal system of the polyacid-based crystal material is a triclinic system; The space group of the polyacid-based crystalline material is P-1: the single package parameters of the polyacid-based crystalline material include: a=11.671(12)-12.148(3), b=13.394(2)-13.591(13), c=17.080(3)-18.132(18), α=86.366(3)-101.532(5), β=74.056(2)-95.030(5), γ=67.280(2)-108.957(5), V=2540.0(8)-2547.9(4), Z=1.

3. A method for preparing a polyacid-based crystalline material, the method comprising: (1) mixing a polyacid, an iron salt, a ligand and water to obtain a mixture; (2) subjecting the mixture to a chemical reaction and obtaining the polyacid-based crystalline material after post-treatment.

4. The method according to claim 3, wherein: In step (1), the iron salt is selected from ferrous acetate and / or ferrous chloride; and / or, the polyacid is selected from Keggin-type vacancy phosphotungstic acid; And / or, the ligand is selected from pyridine-containing or imidazole-containing compounds, preferably 4,4′-(1,3-propanediyl)bipyridine or 1,4-bis(imidazol-1-yl)butane.

5. The method according to claim 3 or 4, wherein: In step (1), the molar ratio of the polyacid to the iron salt is 1:3-6; Preferably, the molar ratio of the polyacid to the ligand is 1:2-3; Preferably, the pH value of the mixture is 2.5-4.

5.

6. The method according to any one of claims 3 to 5, wherein in step (2), the temperature of the chemical reaction is 130-140°C.

7. The method according to any one of claims 3 to 6, wherein in step (2), the reaction time of the chemical reaction is 5 to 7 days.

8. A polyacid-based crystalline material obtained by the method according to any one of claims 3 to 7.

9. Use of the polyacid-based crystalline material according to any one of claims 1, 2 and 8 in the field of degradation of N-methyldiethanolamine.

10. An electrode comprising the polyacid-based crystalline material according to any one of claims 1, 2 and 9.

Citation Information

Patent Citations

  • Preparation method of modification doping lithium ferric phosphate

    CN101630739A

  • POM (polyoxometalate)-based crystal material adopting 3D intercalation structure and preparation method of POM-based crystal material

    CN109092365A

  • Polyacid-based supramolecular material with bifunctional electrocatalytic performance, and preparation method thereof

    CN110128326A

  • Polyacid-based organic-inorganic complex, preparation method thereof, and application of the polyacid-based organic-inorganic complex as photocatalyst in selective oxidation of toluene into benzaldehyde

    CN111644205A

  • Coating jig

    JP1994033298A